Development of a new mouse model for coxsackievirus-induced myocarditis by attenuating coxsackievirus B3 virulence in the pancreas - Pinkert, Sandra; Kaya, Ziya (Cardiovascular research, 2020)
AbstractAims.The coxsackievirus B3 (CVB3) mouse myocarditis model is the standard model for investigation of virus-induced myocarditis but the pancreas, rathe